PacBio high-fidelity near full-length genome sequencing for HIV-1 quasispecies: methodological framework and validation - Zhu, Bo; Wang, Xiaorui; Li, Hanping; Liu, Yongjian; Jia, Lei; Wang, Xiaolin; Li, Jingyun; Zhang, Bohan; Han, Jingwan; Ma, Wei; Li, Lin (Frontiers in Microbiology, 2026)
This study aimed to develop an optimized sequencing workflow for HIV-1 near full-length genome (NFLG) quasispecies, integrating the PacBio Revio platform with a streamlined bioinformatics pipeline to enable precise characterization of the genetic heterogeneity and dynamic evolution of HIV-1 quasispecies. To this end, the HIV-1 NFLG was divided into three segments for high-fidelity amplification and PacBio sequencing. This method achieved stable amplification (positivity rate >80%) in samples with a viral load >1,000 copies/mL and demonstrated applicability to China’s five major epidemic strains and unique recombinant forms (URFs). The adoption of sample-specific asymmetric barcode sequences improved cost-effectiveness, enabling efficient sequencing of 300 to 1,000 samples per sequencing cell. The entire amplification-sequencing workflow exhibited minimal systematic errors (recombination rate <3.5%, average base variation rate <0.1%). Following bioinformatic processing including filtering, clustering, and screening, the sequencing data yielded multiple accurate viral quasispecies sequences with their approximate abundance profiles. Validation studies demonstrated excellent concordance with results from conventional single-genome amplification (SGA) and Sanger sequencing, while showing superior performance in quasispecies-level dual infection detection and recombinant pattern identification. In conclusion, this study developed a PacBio HiFi-based sequencing workflow for HIV-1 NFLG quasispecies, which exhibits robust high sensitivity, accuracy, and reproducibility. This approach provides a powerful tool for deepening understanding of HIV-1 evolution, dissecting genetic diversity, tracing transmission chains, and facilitating precision antiretroviral therapy.